Design, Analysis And Fabrication Of Glass Fiber-Reinforced Pa 6,6 Composite Automotive Clutch Pedals - Syed Shaharuddin, Sharifah Imihezri (2005)
A study of injection number and location is important since it often affects product quality such as weld line and shrinkage as well as process quality such as molding efficiency. This study is also critical because unlike any other processing parameters such as filling speed, pressure and temperature that could be modified instantly, gate location is permanent and any modification equals to increase in cost and time. The main objective of this research is to simulate and analyze the effects of increasing number of gates for a clutch pedal using short glass fiber reinforced PA 6,6. The research compares the effects of a single gated and a double gated mould. A prototype of the composite clutch pedal model is then fabricated and compared with the simulation works. In order to achieve the above-mentioned objectives, two numerical softwares will be used in this study. Moldflow Plastic Insight (MPI) software is used to investigate the effects of mold design on fill time, pressure, temperature, weld line, air traps and fiber orientation and distribution while LUSAS software is used to analyze stress distribution for pedal profiles and rib patterns. The studies show that there are many advantages and disadvantages associated with the design of single and double gated mold. Firstly, a mold designed with a single gate is advantageous in terms of flow balance, fill time and weld line since it provides a more balanced flow, shorter fill time and shorter length of weld line compared to a double gated mold. However, a double gated mold precedes a single gated mold in terms of injection pressure, part shrinkage and trapped air. The study revealed that a double gated mold reduces the required injection pressure as well as pressure variation, hence a lower volumetric shrinkage. Such design also produces less amount of trapped air. Finally, the comparison study of simulation and actual model showed great consistency in terms of fill time, air traps and weld line formations.